2014
DOI: 10.3171/2013.10.peds13303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of skull base development on endonasal endoscopic surgical corridors

Abstract: Object Scarce morphometric data exist on the developing skull base as a corridor for endonasal endoscopic approaches (EEAs). Furthermore, the impact of skull base lesions on its development has not been assessed. The authors describe a novel set of anatomical parameters characterizing the developmental process as well as the utility of these parameters in preoperative planning and a feasibility assessment of EEAs for neurosurgical treatment of skull base lesions in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
3
46
0
1
Order By: Relevance
“…5 The pneumatization process of the yet rudimental paranasal sinuses model skull base bone structures in a caudal-rostral pattern, while the sphenoid sinus pneumatization is a step-wise process following an anterior-posterior trend. 36 All these make the EEA a challenge to perform when dealing with pediatric craniopharyngiomas.…”
Section: Pediatric Eeamentioning
confidence: 99%
“…5 The pneumatization process of the yet rudimental paranasal sinuses model skull base bone structures in a caudal-rostral pattern, while the sphenoid sinus pneumatization is a step-wise process following an anterior-posterior trend. 36 All these make the EEA a challenge to perform when dealing with pediatric craniopharyngiomas.…”
Section: Pediatric Eeamentioning
confidence: 99%
“…Banu et al recently conducted a large retrospective series involving 107 pediatric patients and found that the nare-vomer distance varied significantly with respect to age, and the nare-sellar distance differed significantly with sex. 4 No differences, however, were noted in nasal restriction sites with respect to age, such as the width between middle turbinates or nasal aperture, suggesting access can be gained to pathology of the anterior craniocervical junction despite age and sex variance provided working angles and distances are favorable. Based on the results of this study, we surmise that the inferior extent of the EN approach is likely increased in individuals at the extremes of age (pediatrics and the elderly) relative to middle-aged individuals and similarly in females compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…Banu and colleagues found both the working angle and distance of the EN corridor differed with age in a pediatric population. 4 As the C1-2 and hard palate relationship predicts the sagittal extent of exposure with EN approaches, we hypothesize that the relationship changes with age, similar to the working angle as described by Banu et al While this relationship likely also changes with respect to sex, as suggested by radiographic studies evaluating normal variance of markers for basilar invagination, 16,25 we also assessed and controlled for sex variation. The present study sought to characterize the anatomical relationship of C-2 and the hard palate with age and sex using sagittal CT.…”
mentioning
confidence: 99%
“…As the use of endoscopic endonasal techniques continues to advance, the pediatric population has benefited from the application of these techniques and technologies to manage their smaller and more complex anatomy. 4 Our study sought to define the costs of EES in the pediatric population to determine if it was a cost-effective model for the patient and the health care system. The average length of stay for our series was 4.5 days with 1.8 days in the ICU.…”
Section: Discussionmentioning
confidence: 99%